Game Day Emotions: Exploring How Fan Attitude Drives Official Merchandise Purchase Through Brand Love (Indonesian Liga 1 Context) - Anggara, Bravilio Fitra; Sugiarto, Catur (Universitas Muhammadiyah Pontianak, 2025)
Indonesia hosts of the largest football fanbases in the world. However, many of the first-division football clubs struggles to generate revenue other than ticket sales. Merchandise sales are one of the potential incomes remains underutilized. Furthermore, many fans still wore counterfeit merchandise of the club they support with pride. This research explores how fans’ attitude influence their intention to purchase official club merchandise, with brand love examined as a mediating factor. Price Sensitivity is also included to compare the emotional and rational influences on purchase intention. This research adopts a quantitative approach to examine these relationships. The finding reveals that fan attitude and brand love both have a positive influence on purchase intention, with brand love serving as an effective mediator. Although price sensitivity negatively affects purchase intention, its influence is weaker compared to emotional factors. This research highlights the importance of emotional connection between fans and clubs in driving official merchandise purchase.